Analisis Aliansi Strategi Jaringan Visa Pada Bank XYZ Dalam Rangka Membangun Citra Perusahaan ( Studi Kasus Pada Nasabah Bank XYZ di Jakarta dan Malang ) - Rukmana, Hillalzy Adlan (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the customer's perception of the network strategy alliance of Visa payments in order to build the image of the company. Customer perception becomes very important in knowing the wants and needs of customers. This study used primary data collected using interview technique. The collected data were analyzed using Miles and Huberman analysis. The result of this research is show that customer perception of Bank XYZ give positive contribution in the development of company image through acceptable new technology which launched it is reviewed through technology acceptance model. Thus, to build corporate image the use of strategy alliance becomes one of the alternative choice. Keyword: Alliance strategy, technology acceptance model, corporate image, Visa, financial institution,